Freshwater biodiversity in western Nepal: A review - Khatiwada, Janak Raj; Adhikari, Jagan Nath; Rijal, Deepak; Sharma, Lila Nath (Nepalese Journal of Zoology, 2021)
Western Nepal is known for its rich freshwater resources that support diverse flora and fauna. Freshwater ecosystems of western Nepal provide multitudes of ecosystem goods, services (irrigation, hydroelectricity, drinking water) to humans, and provide breeding and feeding grounds for many wetland-dependent flora and fauna. But these wetlands are under tremendous pressure mainly due to anthropogenic activities. In this review, we provide a brief overview of the freshwater biodiversity, distributions of wetlands and their status in western Nepal. From this review, we found that western Nepal is rich in freshwater resources and supports diverse flora and fauna. The biologically significant Karnali River is the home of a globally endangered species, the South Asian river dolphin. We also discuss the conservation history of wetlands, identify the gaps, and further suggest priority hotspots for the formulation of future conservation strategies for these ecosystems.